Taxonomia da subclasse Tetractinomorpha (Porifera, Demospongiae) do Arquipélago de Abrolhos, BA, Brasil - Esteves, Eduardo Leal (2003)
ln the present study are described and illustrated the sponges of the Subclass Tetractinomorpha from Abrolhos Archipelago, which integrates the largest and most complex reefal region of the South Atlantic. A key to the identification of the Tetractinomorph species from archipelago is also given. Seventeen species of Tetractinomorpha were identified for the archipelago. Five species are new records for the coast of Bahia. Cliona delitrix Pang, 1973, Terpios fugax Duch. & Mich., 1864 and Timea stenosclera Hechtel, 1969 are new occurrences for the Brazilian coast. Two species are new to science: Stelletta anasteria sp. nov. and Terpios ignis sp. nov. Four species of the genus Tethya Lamarck, 1814 collected on the archipelago are well characterized in another work and are not redescribed here. The Abrolhos Archipelago presents a rich Tetractinomorph fauna in relation to the remaining reefal regions of the Brazilian coast. The Tetractinomorph fauna from Abrolhos Archipelago presents a great affinity to the Caribbean one, but is represented by 35,2% of species that are endemic to the local. The great richness, the endemicity and the heterogeneous distribution of the Tetractinomorph species on the Abrolhos Archipelago reinforce the necessity to protect the local reefs.